The development of an air-jet burner for the high intensity combustion of pulverised coal for a gas turbine. - De Villiers, R. C.(Rocco Catorzia),1838-1902 (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.Ing.) -- University of Stellenbosch, 1965.